Produtividade Científica dos docentes da Universidade Estadual Paulista, câmpus de Assis/SP - Herculano, Rondinelli Donizetti [UNESP]; Norberto, Ana Maria Q. (My University, 2011)
In this work, we analyzed the scientific bibliographic productivity of the Faculdade Ciências e Letras de Assis, Universidade Estadual Paulista (FCLAs-UNESP). We evaluated the scientific productivity of Professors using data retrieved from the Lattes Plataform database (Curriculum Lattes), ISI Web of Science and SCOPUS, books published, chapter of the books published and academic advisory (Master's Thesis and Ph.D. Thesis). Bibliometric evaluations of departments showed a better performance of the total number of papers (indexed in Curriculum Lattes database) by Literature Department (P < 0.05) when compared to Modern Languages Department. The Biological Sciences Department had means higher of the papers indexed by SCOPUS (P < 0.05) and ISI (P < 0.05) when compared to others departments. We also observed that the low h-indexes (P< 0,05) in the humanities areas is result of traditional mode of communication in this area of knowledge, which makes more use of books and proceedings of meetings when compared to natural sciences. These publications are not covered by ISI and SCOPUS. The graduate programs in History and Languages presented means higher of academic advisory (Master's Thesis and Ph.D. Thesis) because are graduate programs consolidated in the 1970's.
Scientific research output of professors of Sao Paulo State Universty, Assis/SP
Keywords: Bibliometric indicators; Periodical index; Scientific publication indicators; advisory committee; bibliographic database; bibliometrics; clinical evaluation; education program; human; information retrieval; interpersonal communication; linguistics; natural science; nursing education; scientific literature; university hospital